2018
DOI: 10.5137/1019-5149.jtn.23127-18.3
|View full text |Cite
|
Sign up to set email alerts
|

Mir-24 reduces serum lipid levels and inhibits brain tissue cells apoptosis of rats with cerebral infarction

Abstract: AIM: To study miR-24 effects on cerebral infarction in rats. MATERIAL and METHODS: A rat middle cerebral artery occlusion model (MCAO) was constructed. Intracerebroventricular stereotactic injection of miR-24 agomir/antagomir was performed in the rat MCAO model. According to different experiences, rats were divided into normal, sham, MCAO, miR-24 agomir and miR-24 antagomir groups. Serum TCH, HDL and TG levels were detected. RESULTS: Comparingthe normal and sham groups, we observed decreased relative miR-24 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…At present, many studies have shown that caspase is abnormally expressed in IS and regulated by multiple miRNAs (58). For example, miR-let-tc-3p, miR-195, miR-24, miR-233, miR-503, etc., have been proved to be related to this process (17,(26)(27)(28)59). miR-130a was upregulated in brain tissue of MCAO rats (60) and X-Linked Inhibitor Of Apoptosis (XIAP) was identified as its target molecule.…”
Section: Alterations In Ncrna Expression Following Ischemic Strokementioning
confidence: 94%
“…At present, many studies have shown that caspase is abnormally expressed in IS and regulated by multiple miRNAs (58). For example, miR-let-tc-3p, miR-195, miR-24, miR-233, miR-503, etc., have been proved to be related to this process (17,(26)(27)(28)59). miR-130a was upregulated in brain tissue of MCAO rats (60) and X-Linked Inhibitor Of Apoptosis (XIAP) was identified as its target molecule.…”
Section: Alterations In Ncrna Expression Following Ischemic Strokementioning
confidence: 94%
“…These included miR-15b [69]; miR-23a/b and miR-27a [70][71][72][73]; miR-126a [74][75][76]; miR24, miR-26a, miR-149 [77][78][79][80][81][82][83][84]; and miR-365 [85]. Additionally, several of these upregulated mi-RNA transcripts have also been shown to be neuroprotective including miRNA 23a, miR-23b, miR-24, and miR-27a [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. Finally, EVs from ISG15 knockdown neurons exhibited downregulation of several mi-RNA transcripts that have been shown to promote microglial or macrophage activation and cytokine secretion or neuronal toxicity (Fig.…”
Section: Isg15 Knockdown Alters Mirna Cargo Of Evs From Ifnγ-treated ...mentioning
confidence: 99%
“…Additionally, several of these upregulated mi-RNA species have been shown to be neuroprotective. For example, miRNA 23a, miR-23b, miR-24, and miR-27a are known to target APAF1 and pro-apoptotic BCL family proteins and thereby prevent neuronal apoptosis, and downregulation of these miRNAs during acute EAE, TBI, spinal cord injury, and stroke is thought to contribute to neuron and neurite loss [86][87][88][89][90][91][92][93][94][95][96][97][98]. Direct protection of neurons has been shown for miR-23a in spinal muscular atrophy [99] and for miR-27a in EAE and TBI by, respectively, reducing excitotoxicity through suppression of glutamate receptor subunits [168] and reducing oxidative injury by suppressing FOXO1 and FOXO3a [100,101].…”
Section: Anti-inflammatory and Neuroprotective Ev-mirnas Decreased By...mentioning
confidence: 99%